Analsis Dampak Masa Kerja Dan Lingkungan Kerja Bagi Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening (Studi Pada Karyawan Pt. Sinar Jaya Inti Mulya Metro) - Mega Crissy Nandaresta; Andiana Rosid; Dharmawan (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to determine the effect of years of service and work environment on employee performance with motivation as an intervening variable for employees of PT. Sinar Jaya Inti Mulya Metro. This type of research is quantitative research. The sample of this research are employees of PT. Sinar Jaya Inti Mulya Metro with 67 employees. Data collection using a questionnaire. Each question is measured using a Likert scale with 5 options. The data analysis method used is path analysis (path analysis) so that the direction and magnitude of the influence of exogenous variables on endogenous variables can be clearly described. The results of the study show that: 1) There is a direct effect of years of service on the work motivation of PT. Sinar Jaya Inti Mulya; 2) There is a direct influence of the work environment on the work motivation of employees of PT. Sinar Jaya Inti Mulya; 3) There is a direct effect of tenure on the performance of employees of PT. Sinar Jaya Inti Mulya; 4) There is a direct influence of the work environment on the performance of employees of PT. Sinar Jaya Inti Mulya; 5) There is a direct effect of work motivation on the performance of employees of PT. Sinar Jaya Inti Mulya. Working period has a direct influence on the performance of employees of PT. Sinar Jaya Inti Mulya of 0.009. The work environment has a direct influence on the performance of employees of PT. Sinar Jaya Inti Mulya of 0.002. Working period has a direct influence on the work motivation of employees of PT. Sinar Jaya Inti Mulya of 0.036. The work environment has a direct influence on the work motivation of PT. Sinar Jaya Inti Mulya of 0.008. Work motivation has a direct influence on the performance of employees of PT. Sinar Jaya Inti Mulya of 0.009.